Relationship between Exposure to Cigarette Smoke in Houses and The Incidence of Hypertension in Housewives - Anugrah Lintang Indrawati; Santi Martini (Universitas Airlangga, 2021)
Background: Hypertension is still a major health problem in the world. One of the factors causing hypertension is exposure to cigarette smoke. Purpose: The aim of this study was to analyze the relationship between cigarette smoke exposure and the incidence of hypertension in housewives in houses in Dampit village. Methods: This research adopted an analytical observational approach. This was a cross-sectional design study. The population for this study was all housewives in Dampit village in March 2020. A total number of 115 housewives was selected using the cluster proportional random sampling technique. The dependent variable was the incidence of hypertension; the independent variables were the duration of cigarette smoke exposure in houses, the number of instances contact was made by being in close proximity to smokers, and the contact duration with smokers. Data collection was done by interviewing respondents using a questionnaire. Data analysis was carried out using frequency tables and Epi Info. Results: The study indicated that there was a relationship between the duration of cigarette smoke exposure (over 33 years) in houses with the incidence of hypertension in housewives (p=0.01; OR=3.52; 95%CI=1.53–8.05). Similarly, there was a relationship established between the number of occasions contact was made by being in close proximity to smokers every day (over three times every day) (p=0.01; OR=36; 95%CI=7.64–168.76) and the contact duration with smokers (p=0.01; OR=8.09; 95%CI=3.13–20.87) with the incidence of hypertension in housewives. Conclusion: There was a link between the duration of cigarette smoke exposure in houses, the number of instances of being in close proximity to smokers every day, and the contact duration with smokers with the incidence of hypertension in housewives in Dampit village.